+0  
 
0
161
1
avatar

-3+2[5+9(-3+2)]

Guest Oct 27, 2017
 #1
avatar+561 
+1

We start with the parentheses.

-3+2=-1

-3+2[5+9(-1)]

Multiply 9*-1=-9

remove the parentheses

-3+2[5-9]

simplify the brackets

5-9=-4

2*-4=-8

remove the brackets

-3-8=-11

-11 is your answer

OfficialBubbleTanks  Oct 27, 2017

16 Online Users

avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.